2016
DOI: 10.1136/esmoopen-2015-000022
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade in small cell lung cancer: is there a light at the end of the tunnel?

Abstract: Small cell lung cancer (SCLC) is a very aggressive disease, characterised by rapid growth, high response rates to both chemotherapy and radiotherapy and subsequent development of treatment resistance in the vast majority of patients. In the past 30 years, little progress has been made in systemic treatments and the established management paradigm of platinum-based chemotherapy has reached an efficacy plateau. Several clinical trials have investigated targeted therapies, without producing clinically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(35 reference statements)
0
16
0
1
Order By: Relevance
“…However, despite having one of the highest mutational burdens, small cell lung cancer (SCLC) is often accompanied by relatively high immunosuppression with low levels of T-cell infi ltration and reduced antigen presentation (9)(10)(11). Consistent with this, clinical trials investigating PD-1 or PD-L1 blockade in patients with SCLC have shown low overall response rates ( 12,13 ).…”
Section: Introductionmentioning
confidence: 95%
“…However, despite having one of the highest mutational burdens, small cell lung cancer (SCLC) is often accompanied by relatively high immunosuppression with low levels of T-cell infi ltration and reduced antigen presentation (9)(10)(11). Consistent with this, clinical trials investigating PD-1 or PD-L1 blockade in patients with SCLC have shown low overall response rates ( 12,13 ).…”
Section: Introductionmentioning
confidence: 95%
“…CTLA-4 was the first immune checkpoint receptor to be targeted by a therapeutic agent 26. Monoclonal antibodies against CTLA-4 (ipilimumab and tremelimumab) are designed to prevent the interaction between CTLA-4 and its ligands (CD80/CD86).…”
Section: Introductionmentioning
confidence: 99%
“…They fall into the broad categories of topoisomerase inhibitors (etoposide, teniposide, doxorubicin, topotecan, irinotecan), platinum agents (cisplatin, carboplatin), vinca alkaloids (vincristine, vinorelbine), and alkylating agents (cyclophosphamide, temozolomide). The role of immunotherapy (such as pembrolizumab or nivolumab with ipilumimab) is beginning to emerge for SCLC [ 92 , 93 ]. However, immunotherapy has not been systematically studied in SCLC CNS metastases.…”
Section: Introductionmentioning
confidence: 99%